2016
DOI: 10.1136/postgradmedj-2016-134105
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of survivin expression in renal cancer patients: a meta-analysis

Abstract: Our results indicate that survivin is of prognostic significance in patients with RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Our results show that high BIRC5 expression is associated with worse prognosis in all three analyzed types of kidney cancer. This is in line with previous results from a meta-analysis on 10 studies containing 1063 renal cancer cases, which demonstrated that high Survivin expression is associated with TNM stage and Fuhrman grade [ 54 ]. Other studies have also found a connection with more aggressive renal tumors and high Survivin expression [ 55 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that high BIRC5 expression is associated with worse prognosis in all three analyzed types of kidney cancer. This is in line with previous results from a meta-analysis on 10 studies containing 1063 renal cancer cases, which demonstrated that high Survivin expression is associated with TNM stage and Fuhrman grade [ 54 ]. Other studies have also found a connection with more aggressive renal tumors and high Survivin expression [ 55 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…In RCC patients, BIRC5 has been identified as a prognostic biomarker for RCC survival in several studies evaluating the association between candidate gene expression and overall survival. The expression of BIRC5 was correlated with pathological grade and clinical stage and was also associated with the progression and poor survival of RCC patients [ 32 , 33 , 34 , 35 ]. Recently, a study examining the early diagnosis and prognostic value of BIRC5 in ccRCC based on Cancer Genome Atlas database and Human Protein Atlas database also showed that BIRC5 expression was significantly higher in ccRCC than in normal kidney tissue and correlated with the clinical stage and pathologic grade of ccRCC [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell carcinoma patients, high BIRC5 expression was associated with increased TNM stage and high Fuhrman grade, which indicates that BIRC5 may be a good prognosis predictor (Ma et al, 2017). Furthermore, BIRC5 has been associated with tumor progression and chemoresistance to temsirolimus, an MTOR inhibitor.…”
Section: Kidney Cancermentioning
confidence: 99%